Identifying key signs of motor neurone disease in primary care: a nested case–control study using the QResearch database - Mei, XW; Burchardt, J; Ranger, TA; McDermott, CJ; Radunovic, A; Coupland, C; Hippisley-Cox, J (BMJ Publishing Group, 2022)
Objective To confirm the symptoms and signs for motor neuron disease (MND) in the Red Flag tool; to quantify the extent to which the key symptoms and signs are associated with MND; and to identify additional factors which may be helpful within the primary care setting in recognition of possible MND and triggering timely referral to neurology specialists.